Review of Sami Pihlströhm, Pragmatic Realism, Religious Truth, and Antitheodicy. On Viewing the World by Acknowledging the Other - Honnacker, Ana (European Journal of Pragmatism and American Philosophy, 2020)
Why do bad things happen, why is there suffering in the world? The problem of evil poses a serious threat to the idea of God as an omnipotent, omniscient and absolutely good being since it had been first articulated. The existence of horrible natural disasters and moral abominations continues to be one of the strongest arguments for atheism. Consequently, attempts of absolving God of the charge are legion: theodicies belong to the essential repertoire of traditional Christian theology and phi.